Strategies for Strengthening Student Permission Discipline by Dormitory Caregivers at Dayah Terpadu Babul Maghfirah - Amin, Muhammad; Riza, Syahrul (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
This research investigates the strategies employed by dormitory supervisors in strengthening the discipline of student permission at Dayah Terpadu Babul Maghfirah. The aim is to identify effective disciplinary strategies and understand the challenges faced by supervisors in their implementation. The study adopts a qualitative approach, using in-depth interviews, observations, and documentation as data collection methods. The results indicate that while the dormitory's permission procedures are well-structured and supported by a digital system, there are still numerous violations, particularly related to students returning late from leave. Dormitory supervisors implement a combination of advice, warnings, and punishments such as memorizing or writing the content of the Qur'an as disciplinary measures. These strategies have proven effective in increasing student awareness and responsibility regarding permission rules. However, challenges persist, such as a lack of support from students' guardians and leniency from supervisors. This research highlights the importance of firm, consistent strategies to foster discipline, particularly in the area of student permission within Islamic boarding schools